Using quantitative indicators to measure the efficiency of the road network in Babil Governorate - Abdul-Qider Aziz, Huda (International Journal of Psychosocial Rehabilitation, 2020)
Measuring the efficiency of the transport system is one of the most important measures, which has received great attention from countries, due to their great and vital role in the sustainability of the economic, commercial and agricultural movement of any country, and when any country has an efficient transport system, it is able to meet the needs of its population. With regard to the study area, it became clear that the road density in relation to the area is high compared to the average global density, while the road density for the population was low compared to the global level while the individual’s share of the road was low, and through an analysis of the degree of correlation using the beta coefficient, it proved that there is a transport network interconnected, whereas the use of the beta indicator indicates a complete correlation in the transport system network in the study area.